A cache of jewels and other collective nouns - Heller, Ruth; Hancock, Pat (Scholastic-TAB Richmond Hill, Ont., 1989)
"A Cache of Jewels and Other Collective Nouns" by Ruth Heller is a whimsical and educational exploration of the English language, particularly focusing on collective nouns. Through vibrant illustrations and engaging text, Heller introduces readers to a variety of collective nouns$1 (Bunique terms that describe groups of animals, objects, or people.s